Pengaruh Citra Bank dan Kualitas Layanan Terhadap Kepuasan dan DampaknyaTerhadap Word Of Mouth (Studi Pada Nasabah BNI KCP Sekadau) - tri yudhi bestary (Equator Journal of Management and Entrepreneurship (EJME), 2020)
This research aims to determine the effects of Service Quality and Bank Image variables on customer Satisfaction and the impact on Word of Mouth (WOM). This Research uses quantitative approach with causal design that aims to test theories, build facts, show relationship between variables. This study uses SPSS 16.0 analysis tools with path analysis regression models. Using primary data, the distribution of data collection used is the questionnaire method. The sample used includes 100 active customers at BNI KCP Sekadau. The results indicate that Service Quality and Bank Image variable have a positive and significant effect on customer Satisfaction and that Service Quality and Bank Image variables have no significant impact on WOM. Finally, the Satisfaction variable has a positive and significant effect on WOM.